FUNGSI MUSIK DALAM RITUAL TIBAN DI DESA PURWOKERTO KECAMATAN NGADILUWIH KABUPATEN KEDIRI - Viesta Agustina; Muhammad Nur Salim (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2020)
The article entitled "The Function of Music in Tiban Rituals in Purwokerto Village, Ngadiluwih District, Kediri Regency" focused on the issue of Tiban ritual forms, Tiban ritual music performance and the function of Tiban ritual music. The results showed that the Tiban ritual was held during the long dry season with the aim for asking for rain through whipping by the perpetrators or what is called petiban. The people believe that the Tiban ritual can bring rain by means of media of blood dripping on the ground. Tiban music has several motifs in the wasp structure that characterizes it. Tiban music has an important function in Tiban rituals. The functions of music include the function of emotional expression, aesthetics, communication, physical reaction, legalization of social institutions and religious ceremonies, cultural sustainability, and community integration.